1989
DOI: 10.1002/1097-0142(19890315)63:6<1161::aid-cncr2820630620>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

DNA flow cytometry as a predictor of outcome of stage I renal cell carcinoma

Abstract: The features most frequently used in predicting the outcome of renal cell carcinoma are stage at presentation and nuclear grade. Recently DNA ploidy pattern, as detected by DNA flow cytometry has also been shown to be predictive. In this study DNA flow cytometry was performed on formalin-fixed paraffin-embedded tissue from 50 patients with Stage I renal cell carcinoma for whom long-term follow-up data were available. Two were eliminated for technical reasons. Of the 48 evaluable tumors, 25 (52%) were diploid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
6

Year Published

1989
1989
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 25 publications
(3 reference statements)
0
9
0
6
Order By: Relevance
“…10, 30 The differences in survival with tumor size using older those of Rainwater et al, who also found that DNA ploidy did not correlate with survival in clear cell staging systems now are accounted for in the revised TNM system, in which tumors confined to the kidney RCC confined to the kidney. 37 Similarly, in more recent studies of localized RCC, DNA ploidy did not measuring°7 cm in greatest dimension correspond to a classification of pT1 and tumors measuring ú 7 predict survival.…”
Section: Discussionmentioning
confidence: 97%
“…10, 30 The differences in survival with tumor size using older those of Rainwater et al, who also found that DNA ploidy did not correlate with survival in clear cell staging systems now are accounted for in the revised TNM system, in which tumors confined to the kidney RCC confined to the kidney. 37 Similarly, in more recent studies of localized RCC, DNA ploidy did not measuring°7 cm in greatest dimension correspond to a classification of pT1 and tumors measuring ú 7 predict survival.…”
Section: Discussionmentioning
confidence: 97%
“…Cox pro-portional hazards regression analysis showed DNA ploidy to be an independent predictor of adverse outcome; in a previous study restricted to Stage I renal cell carcinomas and so analyzed, we found DNA ploidy to be significant but not independent of tumor size and nuclear grade. 38 Our finding that the mean time to death from renal cell carcinoma was approximately twice as long in the diploid cases than in the nondiploid ones (62.3 months versus 34.1 months) is in keeping with the results of Ljungberg et Several systems for grading renal cell carcinoma have been devised, 1 9 , 2 3 3 2 4 3 3 6 and most have correlated with tumor behavior. ' 9,23,24,27-29,31,34,35 In this study we used the nuclear grading system proposed by Fuhrman et ~1 .…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] DNA ploidy level can also be determined by means of the computer-assisted microscopy of Feulgen-stained nuclei. 20,21 The aim of the present work was to determine, on a series of 65 RCCs, what type(s) of quantitative variables provided by computer-assisted microscopic analysis of Feulgen-stained nuclei contribute(s) diagnostic information and could therefore increase the accuracy of nuclear grading.…”
Section: Introductionmentioning
confidence: 99%